Inside book publishing [electronic resource] - Clark, Giles N. [ (Giles Noel)]; Phillips, Angus , 1961- (Routledge, 2008)
Addresses issues such as globalization of publishing and the impact of the internet. This edition covers: how the industry has evolved; publishing functions - editorial, design and production,